(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the current status of care and analyze factors related to maternity care at Vinmec Times City International General Hospital in 2025. Method: A cross-sectional descriptive study was conducted on 400 pregnant women at the Department of Obstetrics and Gynecology, Vinmec Times City International General Hospital. Using a questionnaire and structured interviews. Results and conclusions: The rate of full-term births was 92%, and premature births was 6.25%. Among common accompanying diseases, gestational diabetes was the most common with 13%, followed by hypertension with 1.25%. Vital signs (pulse, blood pressure, breathing rate, SpO2) of the mothers after the first 3 hours after birth in normal condition reached over 60%. The condition of the incision and episiotomy wound was dry and good at 96.25%; the mothers had moderate or low lochia discharge at 73.75%, and high lochia discharge at 26.25%. 100% of the mothers had good uterine contractions after giving birth. Over 85% of mothers were counseled and understood correctly about family planning after cesarean section. There was a correlation between pregnant women with comorbidities receiving better care than pregnant women without comorbidities (OR = 3.296; 95%CI = 1.53-8.15; p < 0.05).